Holocene history of Taxus baccata in the Basque Mountains (Northern Iberian Peninsula) - Pérez-Díaz, Sebastián; López-Sáez, José Antonio; Ruiz-Alonso, Mónica; Zapata, Lydia; Abel Schaad, Daniel (Lazaroa, 2013)
In this paper we offer an overview of Holocene evolution of a species, yew (Taxus baccata L.) in a very specific sector of the Northern Iberian Peninsula, the Basque Mountains. In order to this, we have collected all macro and microrremain evidences of the presence of yew within its chronological framework. Results suggest the existence of a period of expansion of yew populations during the Middle Holocene and a regression phase during Late Holocene.